Investigation the potential role of some medicinal plants extracts in regulating serum lipid profile in female albino rats - Hameed, Shahad Imad; Al-Shahwany, Ayyad W.; Salih, Sabah Jawad (Iraqi Journal of Science, 2019)
Strong evidence showed that many medicinal plants have the potential to reduce hyperlipidemia disease. The aim of this study was to determine the hypolipidemic activity of aqueous extracts of Fucus vesiculosus, Coleus forskohlii, Curcuma longa L., Rosmarinus officinalis L., Camellia sinensis L. and Melissa officinalis L. on lipid profile in serum taken from the blood of rats. Fifty-seven female albino rats were divided into 19 groups, each with three rats, that were treated orally with an aqueous plant extract in three different doses, except the control group which was treated with normal saline only. The chemical compositions of these extracts were analyzed using High Performance Liquid Chromatography (HPLC).The results showed that the dose of 5 mg/kg ofCurcuma longa was the powerful extract which reduced levels of cholesterol (CHO) and low-density lipoprotein (LDL) in serum rats' blood by 31 and 55%, respectively, compared with the control treatment. While, the effective extract to reduce triglycerides (TG) level was that ofFucus vesiculosus(50mg/kg) which reduced TG by 38% compared with the control. Also, Melissa officinalis(50 mg/kg ) extract reduced 30% of very low-density lipoprotein (VLDL) level as compared to the control treatment. In addition, Coleus forskohlii(100 mg/kg) extract increased high-density lipoprotein (HDL) level by 115% after being orally given to rats for four weeks. The results of the study indicated significant differences among the concentrationsof the secondary compoundswithin their extracts, which maybe responsible for the observed variations of hypolipidemic activity for each extract. Based on these results, further investigation should target understanding the mechanismsby which these plants can be used as food additives and as dietary supplement.